2017
DOI: 10.3906/biy-1609-74
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and apoptotic effects of endemic Centaurea fenzlii Reichardt on the MCF-7 breast cancer cell line

Abstract: Materials and methods Cell culture and chemicalsThe MCF-7 breast cancer cell line was provided by Prof Dr Engin Ulukaya (Uludağ University, Turkey). MCF-7 cells were cultured in DMEM with penicillin G (100 U/mL), streptomycin (100 mg/mL), L-glutamine, and 5% fetal calf serum at 37 °C in a humidified atmosphere containing 5% CO 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
1
5
0
1
Order By: Relevance
“…19 The cytotoxic and apoptotic properties of a plant Centaurea fenzlii have been determined on the breast cancer MCF-7 cell line and it has exhibited significant cytotoxic effects and it was found that the major component of the plants sample was hispidulin. 20 In our study, Hispidulin reduced the viability of four different cancer cell lines, significantly. The breast cancer MCF-7, osteosarcoma MG-63, pancreatic PACA-44, and alveolar rhabdomyosarcoma Rh30 cell lines showed a moderate reduction of cell viability in the range of 20 to 50%.…”
Section: Nmr Data For β-Sitosterol (1)supporting
confidence: 49%
“…19 The cytotoxic and apoptotic properties of a plant Centaurea fenzlii have been determined on the breast cancer MCF-7 cell line and it has exhibited significant cytotoxic effects and it was found that the major component of the plants sample was hispidulin. 20 In our study, Hispidulin reduced the viability of four different cancer cell lines, significantly. The breast cancer MCF-7, osteosarcoma MG-63, pancreatic PACA-44, and alveolar rhabdomyosarcoma Rh30 cell lines showed a moderate reduction of cell viability in the range of 20 to 50%.…”
Section: Nmr Data For β-Sitosterol (1)supporting
confidence: 49%
“…Antiproliferative activity of an apolar organic extract from aerial parts was shown on two cancer cell lines, namely acute lymphoblastic leukemia and its multidrug-resistant subline likely attributed to aguerin B and cynaropicrin contents (33). Similarly, aerial parts of endemic Centaurea fenzlii Reichardt collected from East Anatolian region indicated significant cytotoxic effects on the MCF-7 breast cancer cell line (34). Hispidulin was reported as the main component (34).…”
Section: Asteraceaementioning
confidence: 97%
“…Similarly, aerial parts of endemic Centaurea fenzlii Reichardt collected from East Anatolian region indicated significant cytotoxic effects on the MCF-7 breast cancer cell line (34). Hispidulin was reported as the main component (34). In the study of Sen and coworkers (2015), chloroform and methanol extracts of another endemic Centaurea species, C. kilaea Boiss.…”
Section: Asteraceaementioning
confidence: 97%
“…Centaurea genus is widely distributed in Turkey. It has many medicinal properties including anti-inflammatory, antidiabetic, digestive, antipyretic, cytotoxic, anti-dandruff and antibacterial (11)(12)(13). Centaurea virgata Lam.…”
Section: Introductionmentioning
confidence: 99%